+0  
 
0
83
1
avatar+112 

Use the product-to-sum (NOT SUM-TO-PRODUCT) formulas to write the given expression as a product.

 

\(12\sin\frac{\pi}{6}\sin\frac{\pi}{6}\)

 

A. \(-6\sin\frac{\pi}{12}\)

B. \(6\sin\frac{\pi}{6}+6\cos\frac{\pi}{6}\)

C. \(6-6\cos\frac{\pi}{12}\)

D. \(6+6\cos\frac{\pi}{12}\)

 Jan 13, 2021
 #1
avatar
+1

sinasinb = 1/2 [cos ( a-b) -cos(a+b)]

 

               = 1/2 * 12   ( cos 0 - cos pi/3)

                6  - 6 cos pi/3                            <============== Don't see that as an answer ....they MIGHT have intended  C.

 Jan 13, 2021

52 Online Users

avatar
avatar
avatar